Deterministic service level agreement: indicator classification in private networks for vertical industry - ZHANG Mufeng; LI Hongxing; WANG Ke; LI Xiaoliang; LIU Yaqiong; HU Yihong; SHOU Guochu (Dianxin kexue)
Meeting the differentiated deterministic service quality experience of customers in different industries in an economically effective manner is conducive to promoting the construction of a vertical industry deterministic private network. In the face of various segmented industries and different dimensions of deterministic service quality requirements, the classification and grading of SLA(service level agreement) indicators are very important. Firstly, various types of application scenarios of deterministic service in vertical industries were summarized, and indicator requirements analysis was conducted for each type of business. Then, a deterministic SLA indicator system was proposed and a hierarchical design scheme for each indicator was summarized to solve the problem of insufficient reflection of deterministic attributes in current network SLA indicators, and help reducing the difficulty of understanding and aligning indicators between industry customers and service providers, and enable the network to meet the deterministic service needs of different industries. Finally, prospects for future work were presented.